Research on the age characteristics of the Olympic champions in men weigtlifting - Shiyong, Y. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Systematic research male performance patterns and age characteristics of Weightlifting Champions in Olympic Games, and reached exact conclusions, with the purpose of exploring and mastering men excellent lifter's basical regularity of the improvement performance, predicting the future development trend, which has significanly meaning for guiding weightlifting training. Methods We use scientific research methods of documents(collecting relative information from over 100 articles and 40 books, as well as the official webnet of IWF), investigation, logic and statistics on related matters of Olympic Weightlifting Competition from 1896 to 2000. Results And Discussion 129 male weightlifting champions from 30 nations have appeared during the period of 104 years of the Olympic Games from 1896 to 2000 (P.S. 436 medals of Weightlifting had been given out ,148 gold medals included, the silver and the bronze medals are 144 respectively ). 3 among them won 3 times Olympic champions ( Suleymanoglu Naim from Turkey. Dimas Pyrros and Kakiasvilis kakhi both from Greece) ,13 among them won Olympic champions twice. The 129 men lifters average age of winning the Olympic championship is 25.7± 3.65, among them the oldest one is 36 (Pljukfelder Rudolf from U.S.S.R ) and the youngest one is less than 20 (Zeng Guoqing from China ). The average years of training to obtain the championship is 10.72± 2.45. Analyzing the 3 men who reached the olympic champion three times and 13 men who reached the champion twice, we know that their average training years to win their first Olympic gold medales is 9.81±2. Lifters started to train from 16 ~17 years old in 1950s and to 11~12 in 1980s. In recent 40 years the Olympic champion's average age fall down from 27~28 to 24.5. Conclusions From above analysis and research, the conclusions are reached as follows: 1. 129 male lifters average age of winning the Olympic championship is 25.7±3.65. the years of training to win the championship average is 10.72±2.45. 2. The earlier the starting age of weightlifting training, the younger age of the lifters to have a good result, vice versa. 3. It predicted that male weightlifting champions of the future Olympic Games will be at the age of 23~24.